2008
DOI: 10.1126/science.1163952
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Spatial Self-Organization and Its Emergent Effects in Mussel Bed Ecosystems

Abstract: Spatial self-organization is the main theoretical explanation for the global occurrence of regular or otherwise coherent spatial patterns in ecosystems. Using mussel beds as a model ecosystem, we provide an experimental demonstration of spatial self-organization. Under homogeneous laboratory conditions, mussels developed regular patterns, similar to those in the field. An individual-based model derived from our experiments showed that interactions between individuals explained the observed patterns. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
207
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(213 citation statements)
references
References 25 publications
5
207
0
1
Order By: Relevance
“…Self-organised patterns are noted in beds of blue mussel populations, Mytilus edulis, on intertidal ats with signi cant variability in mussel density observed on larger scales of meters, but with no apparent within-cluster di erence. It is suggested that the interaction between individual mussels is the only underlying mechanism of such pattern formation (Gascoigne et al 2005, van de Koppel et al 2008). In the quest of revealing irregular spatial distributions, the most intuitive starting point would be amongst cyclic populations, as they tend to be regulated by highly nonlinear interactions (Bjørnstad et al 2002).…”
Section: Simulationsmentioning
confidence: 99%
“…Self-organised patterns are noted in beds of blue mussel populations, Mytilus edulis, on intertidal ats with signi cant variability in mussel density observed on larger scales of meters, but with no apparent within-cluster di erence. It is suggested that the interaction between individual mussels is the only underlying mechanism of such pattern formation (Gascoigne et al 2005, van de Koppel et al 2008). In the quest of revealing irregular spatial distributions, the most intuitive starting point would be amongst cyclic populations, as they tend to be regulated by highly nonlinear interactions (Bjørnstad et al 2002).…”
Section: Simulationsmentioning
confidence: 99%
“…In these systems, the number of potentially cooperating neighbours depends on the spatial scale and distribution pattern of the population. In many systems, the spatial pattern results from the active movement of organisms (Theraulaz et al 2003;Jeanson et al 2005;van de Koppel et al 2008;de Jager et al 2011;Hemelrijk and Hildenbrandt 2012). Accordingly, the movement strategies of these organisms can indirectly affect the number of neighbours an individual will encounter.…”
Section: Introductionmentioning
confidence: 99%
“…First, we investigate how the aggregation strategy of mussels affects the spatial pattern and, in particular, the number of neighbours available for cooperation. Aggregation in mussels typically leads to the formation of a spatial pattern consisting of regularly spaced strings and clumps (van de Koppel et al 2005. With an individual-based model (IBM), we investigate how the number of neighbours a mussel experiences is related to this self-organized pattern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations